Technical Guidance for Preparing Merdeka Curriculum-Based Teaching Modules for Middle School Dance Subjects in Serang City - Triana, Dinny Devi; Haerudin, Deden; Soleha, Rochmah (Abdi Masyarakat, 2025)
The purpose of this community service activity is to enhance teachers' ability to create Teaching Modules as a replacement for the Lesson Plans that have been commonly used in the previous curriculum. The Merdeka Curriculum needs to be understood by teachers in relation to the formulation of Learning Objectives, Learning Objective Pathways, teaching materials, teaching methods, and assessment of the learning process and outcomes. The systematic preparation of teaching modules as a substitute for Learning Plans has not yet been mastered by teachers, resulting in the available Merdeka Mengajar Platform (PMM) being less comprehensive in providing an overview of Learning Planning. Based on the aforementioned issues, this technical guidance activity involves mentoring the dance teacher learning community in Serang City to develop teaching modules in accordance with Phase D as specified in the Merdeka Curriculum. The activities begin with the analysis and mapping of Learning Outcomes in Phase D, setting learning objectives and their progression, and finally compiling ready-to-use teaching modules, which can serve as a reference for other dance teachers in Indonesia.